Restorative Justice in Civil Disputes: A Progressive Approach to Civil Law - Rizki Wahyudi; Natasya Yunita Sugiastuti; Munira; Reza Kautsar Kusumahpraja; Rafiqi (Universitas Muhammadiyah Palu, 2026)
Restorative justice is an approach to dispute resolution that emphasizes the restoration of relationships between conflicting parties rather than prioritizing punitive outcomes or adversarial judgments. In the context of civil law, this approach offers a more humane, participatory, and solution-oriented alternative, focusing on achieving mutually beneficial and sustainable agreements. This article aims to examine and analyze the application of restorative justice in civil disputes as part of the development of a progressive legal paradigm in Indonesia. The research employs a normative legal method using both conceptual and statutory approaches, supported by a comprehensive review of relevant academic literature. The analysis is conducted qualitatively to explore the relevance of restorative justice principles in civil law practices and their contribution to achieving substantive justice. The findings indicate that the implementation of restorative justice in civil disputes holds significant potential to enhance the effectiveness of dispute resolution mechanisms. It not only provides legally acceptable outcomes but also helps preserve social relationships between the parties involved. Furthermore, this approach aligns with the principles of progressive law, which prioritize justice, fairness, and social benefit over rigid procedural formalities. However, its implementation still faces several challenges, including the lack of explicit regulatory frameworks, limited understanding among legal practitioners, and low public awareness regarding non-litigation dispute resolution mechanisms. Therefore, strengthening both regulatory support and practical implementation is necessary to optimize the role of restorative justice within Indonesia’s civil law system.